2017
DOI: 10.2967/jnumed.117.192534
|View full text |Cite
|
Sign up to set email alerts
|

Functional Optical Imaging of Primary Human Tumor Organoids: Development of a Personalized Drug Screen

Abstract: Primary tumor organoids are a robust model of individual human cancers and present a unique platform for patient-specific drug testing. Optical imaging is uniquely suited to assess organoid function and behavior because of its subcellular resolution, penetration depth through the entire organoid, and functional endpoints. Specifically, optical metabolic imaging (OMI) is highly sensitive to drug response in organoids, and OMI in tumor organoids correlates with primary tumor drug response. Therefore, an OMI orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 39 publications
(89 reference statements)
0
26
0
Order By: Relevance
“…Organoids can provide a platform for drug testing of individual tumors in a short period of time before or in parallel to implementation of clinical therapy for a PDAC patient. Although some groups have reported a 1-week time period (from biopsy to drug selection), 72 large-scale drug screens could be conducted within 3–4 weeks after receiving the biopsy of a given patient. This approach has the potential to identify individual therapeutic vulnerabilities (based on the genetic mutation profile and drug response in organoids), or to define second or third lines of treatment if standard therapy does not work.…”
Section: Applications Of Three-dimensional Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organoids can provide a platform for drug testing of individual tumors in a short period of time before or in parallel to implementation of clinical therapy for a PDAC patient. Although some groups have reported a 1-week time period (from biopsy to drug selection), 72 large-scale drug screens could be conducted within 3–4 weeks after receiving the biopsy of a given patient. This approach has the potential to identify individual therapeutic vulnerabilities (based on the genetic mutation profile and drug response in organoids), or to define second or third lines of treatment if standard therapy does not work.…”
Section: Applications Of Three-dimensional Organoidsmentioning
confidence: 99%
“…It is also capable of detecting heterogeneity, identifying the nonresponding subclones, and differentiating between premalignant and invasive lesions. 62 , 73 Walsh et al 74 reported that optical metabolic imaging has high sensitivity for detecting metabolic changes 24–72 hours after exposure to effective drugs, and this response is correlated with the expected responses (ie, based on HER2 expression in breast cancer). Furthermore, it has been shown that optical metabolic imaging analysis can differentiate between cell types and drug response.…”
Section: Applications Of Three-dimensional Organoidsmentioning
confidence: 99%
“…Specifically, optical metabolic imaging (OMI) is a multiphoton microscopy to detect the intrinsic fluorescence intensities and lifetimes of nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD), coenzymes of metabolic reactions. OMI has been shown to be a sensitive technique to assess drug-induced changes in cellular metabolism of organoids to predict the action of anticancer compounds 28,32 . However, this technique does not allow direct imaging of drugs and drug metabolites to evaluate the distribution and metabolic properties of therapeutics in organoids.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a minimal amount of tumor cells are required to form spheroids 63,64 , and cutaneous cells can easily be obtained from a small biopsy to produce skin. Spheroids and organoids are already tested as tools to optimize treatment for each patient, but the role of TME is not recapitulated in these models.…”
Section: Discussionmentioning
confidence: 99%